Effectiveness of Mhealth on Immunization Target Tracking Which Affects Drop Out and Left Out Numbers in Rural and Urban Areas at The Public Health Center Level, Indonesia - Sugita Pattah; Arsin Andi Arsunan; Maria Leida Ida; Ansariadi; Ishak Hasanuddin; Syam Aminuddin (Medsci Publications, 2023)
Background: The M-KIA (Mobile-Tracking Immunization Target) has features aimed at reducing the number of DO (Drop Out) and LO (Left Out) children. The purpose of this study was to analyze the effectiveness of using the M-KIA application in urban and rural areas. Method: We conducted a quasi-experiment with control group non-equivalent. The population were all parents with children aged 0-36 months who are DO or LO in the working area of the Bantaeng Public Health Center (PHC), while the number of samples is 226 people. The sampling technique was multistage random sampling. Data were analyzed by the Fisher exact test using STATA. Results: There is a significant relationship between the use of M-KIA on DO targets in rural areas (p = 0.000<0.05) and in urban areas (p = 0.002<0.05). On the LO target, the use of M-KIA showed a significant relationship in rural areas (p = 0.015 <0.05) while in urban areas the data was not significant (p = 0.612 <0.05). Conclusion: This study shows that the use of mhealth can reduce the number of DO and LO. Further research is recommended to be conducted to assess the level of usability to assess retention of use with users and admins.